(untitled) (Bioresearch Communications, 2023)
The widespread consumption of milk for its nutritional value and health benefits brings the risk of milk-borne diseases due to the presence of various microorganisms, including antibiotic-resistant pathogens. This has led to an increased focus on ensuring the safety of milk products across the supply chain by dairy industries. The study aimed to evaluate microbiological parameters and detect multi-antibiotic-resistant pathogens at three specific supply points and to explore the association between the presence of residual antibiotics and the resistant isolates in milk samples. About 50 milk samples, including raw, soon-after-processed, packaged marketed pasteurized, and UHT milk, were subjected to microbiological analysis. This involved assessing the total bacterial count (TBC) and total coliform count (TCC), conducting antibiotic susceptibility tests through disk and well diffusion assays, detecting virulence genes in multi-antibiotic resistant isolates using gene-specific PCR, and analyzing residual antibiotics by HPLC. The study revealed that the quality of raw milk samples was unacceptable (TBC >4.5x107 CFU/mL and TCC >5.6x104 CFU/mL), while pasteurized samples from processing plants had lower counts than those from retail stores (TBC >5x105 CFU/mL and TCC >1.6x104 CFU/mL) indicating post-pasteurization contamination. About 70.37% of the isolates were Gram-negative, with Escherichia coli (21.4%) and Vibrio (18.8%) being the most prevalent. Resistance to antibiotics was substantial, particularly against ampicillin (86.3%), tetracycline (76%), and ciprofloxacin (58.9%). Gene-specific PCR analysis detected uidA, oprL, and oprI virulence genes in multi-drug-resistant Escherichia coli and Pseudomonas sp. respectively. The study also revealed a direct association between the presence of residual antibiotics and the resistant isolates, emphasizing the need for dairy industry improvements. As high bacterial counts in milk can pose health risks by fostering antibiotic-resistant pathogens, it is essential to mitigate microbiological contamination in the milk supply chain through the implementation of various precautionary measures. Bioresearch Commu. 10(1): 1462-1473, 2024 (January)